2019
DOI: 10.5114/aoms.2019.89777
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month kinetics of circulating fibrosis-linked microRNAs (miR-21, miR-29, miR-30, and miR-133a) and the relationship with extracellular matrix fibrosis in dilated cardiomyopathy

Abstract: Introduction: A single measurement of any biomarker may not reflect its full biological meaning. The kinetics of fibrosis-linked microRNAs and their relationship with extracellular matrix (ECM) fibrosis in dilated cardiomyopathy (DCM) have not been explored. Material and methods: We evaluated 70 consecutive DCM patients (48 ±12.1 years, left ventricular ejection fraction 24.4 ±7.4%). All patients underwent right ventricular endomyocardial biopsy in order to quantify ECM fibrosis and measure collagen volume fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although miR-29 is upregulated in fibrotic tissue, serum level has not frequently been reported to be correlated with fibrosis. Rubis et al found decreased miR-21-5p and elevated miR-29b in biopsy-proven fibrotic dilated cardiomyopathy patients [ 53 ]. Therefore, miR-29b-3p could be a promising therapeutic target for allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although miR-29 is upregulated in fibrotic tissue, serum level has not frequently been reported to be correlated with fibrosis. Rubis et al found decreased miR-21-5p and elevated miR-29b in biopsy-proven fibrotic dilated cardiomyopathy patients [ 53 ]. Therefore, miR-29b-3p could be a promising therapeutic target for allograft dysfunction.…”
Section: Discussionmentioning
confidence: 99%